Modern aspects of the choice of mucoactive cough therapy in pediatric practice - L.V. Besh; O.I. Matsyura (Zaslavsky O.Yu., 2018)
The article presents the main approaches to the administration of mucoactive cough therapy in pediatric practice. Some of medicines most commonly used in children such as ambroxol and carbocysteine and their combination are described. We conducted our research of the efficacy of three mucoactive agents such as ambroxol, carbocysteine and their combination (Pectolvan C) in the treatment of acute respiratory viral infections in children aged 2 to 6 years old, which were accompanied by a productive cough with viscous sputum that was difficult to expectorate. It has been proven that the most effective in such cases is the combined drug Pectolvan C.